PERAN GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS V SDN 4 KUTOHARJO REMBANG - Shofa, Nawwara; Prasetyo, Singgih Adhi; Huda, Choirul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted based on the importance of teachers’ roles in enhancing students’ learning motivation, which significantly influences academic and non-academic achievement. The problem addressed in this study is how teachers contribute to increasing the learning motivation of fifth-grade students at SDN 4 Kutoharjo Rembang and what strategies they use to motivate students. The objectives of this research are to describe the roles of teachers in motivating fifth-grade students and to identify the methods applied to foster students’ learning motivation. This study employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the fifth-grade teacher and students at SDN 4 Kutoharjo Rembang. The validity of the data was ensured through source triangulation by comparing data obtained from different sources. The results of the study indicate that teachers play significant roles as motivators, facilitators, and classroom managers by encouraging students to be active in learning activities, creating a conducive classroom atmosphere, applying varied teaching methods, showing enthusiasm in teaching, providing rewards, and designing engaging classroom activities. Furthermore, teachers motivate students through grades, prizes, competitions, and appropriate punishments. These efforts contribute to increasing students’ learning motivation and supporting their academic and non-academic achievements.